2001
DOI: 10.1590/s0103-84782001000200024
|View full text |Cite
|
Sign up to set email alerts
|

TOPOGRAFIA DAS ABERTURAS DOS DUCTOS PAROTÍDICOS DE UM LOBO GUARÁ (Chrysocyon brachyrus ILLIGER, 1811)

Abstract: Estudou-se a topografia dos pontos de abertura dos ductos parotídicos no vestíbulo da boca de um lobo guará (Chrysocyon brachyrus), fêmea, adulto, proveniente do Zoológico do Parque do Sábia, da cidade de Uberlândia, Minas Gerais, Brasil. Realizaram-se incisões horizontais nas paredes do vestíbulo da boca, a cada lado, até um ponto das comissuras labiais que permitiam a identificação das aberturas dos ductos parotídicos, bem como suas relações com as faces vestibulares dos dentes pré-molares e molares superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…In P. cancrivorus, the gland and the outlet of its duct in the fourth upper premolar shows similarity to the domestic carnivorous dog. In studies such as Santos et al (2001), maned wolf (Chrysocyon brachyrus) showed the opening of the parotid duct at the level of the lateral line of the first upper molar tooth. Through the results, one must consider the existence of topographic variations in relation to the point of confluence of the parotid duct in other individuals of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…In P. cancrivorus, the gland and the outlet of its duct in the fourth upper premolar shows similarity to the domestic carnivorous dog. In studies such as Santos et al (2001), maned wolf (Chrysocyon brachyrus) showed the opening of the parotid duct at the level of the lateral line of the first upper molar tooth. Through the results, one must consider the existence of topographic variations in relation to the point of confluence of the parotid duct in other individuals of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…Em cães domésticos, a topografia do ducto parotídeo encontra-se amplamente documentada por Fernandes Filho et al (1988), Mendonça et al (2004), Silva et al (2008) e Lima et al (2011). Em carnívoros silvestres há poucos relatos na literatura consultada da descrição do local da desembocadura do ducto parotídeo em Chrysocyon brachyurus (Santos et al, 2001), Nasua nasua e Procyon cancrivorus (Santos et al, 2012). Assim, objetivou-se determinar a localização anatômica da papila parotídea do C. thous e L. gymnocercus e comparar os achados com os dados disponíveis em outras espécies carnívoras.…”
Section: Introductionunclassified
“…O conhecimento da localização exata e de possíveis alterações da abertura oral do ducto excretor das glândulas salivares é de grande importância, perante o desenvolvimento do uso de técnicas mais acuradas na detecção de processos patológicos, desde traumáticos, até tumorais da referida glândula ou de suas vias de escoamento (SANTOS; LIMA, 2001;SANTOS et al, 2010b).…”
Section: Introductionunclassified